2005
DOI: 10.1111/j.1525-1438.2005.15234.x
|View full text |Cite
|
Sign up to set email alerts
|

Immature ovarian teratoma in a young girl: very short course and lethal outcome. A case report

Abstract: Immature teratomas of the ovary represent less than 1% of all ovarian teratomas. They contain several tissues that derive from the three embryologic layers: ectoderm, mesoderm, and endoderm. We report the case of a 17-year-old girl who presented with an immature teratoma of the left ovary that recurred 3 months later as an inoperable malignant neuroepithelial peritoneal tumor resembling a glioblastoma. She died 3 weeks after the second explorative operation. The very aggressive course and fast lethal outcome c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Bokhman et al study 4 was one of the most comparable studies to our research as the age group in the former was 13 to 96 years and the mean age was 54.5, whereas in comparison to our study, the age ranged from 19 to 76 years with a mean age of 53.14 years and a median age of 53.50 years. In one of the previous studies by Terzic et al, they have observed immature teratoma in a 17-year-old female, 7 similarly we had reported one such case in a 19-year-old and findings were comparable to the study. According Morice et al, endometrial cancers were more prevalent in patients above 55 years of age.…”
Section: Discussionsupporting
confidence: 91%
“…Bokhman et al study 4 was one of the most comparable studies to our research as the age group in the former was 13 to 96 years and the mean age was 54.5, whereas in comparison to our study, the age ranged from 19 to 76 years with a mean age of 53.14 years and a median age of 53.50 years. In one of the previous studies by Terzic et al, they have observed immature teratoma in a 17-year-old female, 7 similarly we had reported one such case in a 19-year-old and findings were comparable to the study. According Morice et al, endometrial cancers were more prevalent in patients above 55 years of age.…”
Section: Discussionsupporting
confidence: 91%
“…12 Even though high serum value of Ca125 is seen in many benign conditions, there are enough evidences in the literature which give high importance to the value of Ca125 in the evaluation of adnexal mass. [13][14][15][16] In our study, out of all benign adnexal mass, 21.4% were endometriotic cysts that could lead to the increase of CA125 levels in the group of women with benign adnexal masses.…”
Section: Discussionmentioning
confidence: 47%